THE STUDY OF FISCAL VULNERABILITY BASED ON PUBLIC DEBT DYNAMIC EQUATION: EMPRIRICAL EVIDENCE FOR ADVANCED EUROPEAN UNION COUNTRIES - Stoian, Andreea (European Scientific Journal, ESJ, 2013)
This paper aims shedding more light in the understanding and the study of fiscal vulnerability. Therefore, it presents a methodology of assessing vulnerability of fiscal policy using a public debt dynamic equation which allows estimating the primary balance that stabilizes public debt. Calculating the primary gap represented by the difference between the stabilizing and the current primary balance, it can be indicated fiscal vulnerability. It is used annual data ranged for 1971 and 2010 and investigated the vulnerability of fiscal policy for the case of 10 advanced economies in the European Union. The results showed only a few episodes of more severe fiscal vulnerability occurring after the financial turmoil. Most of the data analyzed indicates a normal state of fiscal vulnerability that is not induced by the government’s failure in achieving the stabilizing primary balance but by not aiming at the stabilization of the public debt.